2006
DOI: 10.1098/rsta.2006.1781
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous three-dimensional anatomical and electrophysiological model of human atria

Abstract: Investigating the mechanisms underlying the genesis and conduction of electrical excitation in the atria at physiological and pathological states is of great importance. To provide knowledge concerning the mechanisms of excitation, we constructed a biophysical detailed and anatomically accurate computer model of human atria that incorporates both structural and electrophysiological heterogeneities. The three-dimensional geometry was extracted from the visible female dataset. The sinoatrial node (SAN) and atriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(257 citation statements)
references
References 28 publications
3
248
0
6
Order By: Relevance
“…The computed atrial wall thickness in the left atrial appendage was found to be affected by the extremely complex and trabecular atrial anatomy,30 and thus wall thickness of the left atrial appendage was not reported. The atrial cellular activation model is based on a simplified Fenton‐Karma model, not biophysics‐based cellular models10, 12 for the sake of computational efficiency, although it was validated by optical mapping data in this study and widely used by us15, 27 and others 28. Additionally, because of a single uniform cellular model used across the atria in the computer model, APDs in some regions (eg, distal side of PV sleeves) may not match well between modeling and optical mapping.…”
Section: Discussionmentioning
confidence: 99%
“…The computed atrial wall thickness in the left atrial appendage was found to be affected by the extremely complex and trabecular atrial anatomy,30 and thus wall thickness of the left atrial appendage was not reported. The atrial cellular activation model is based on a simplified Fenton‐Karma model, not biophysics‐based cellular models10, 12 for the sake of computational efficiency, although it was validated by optical mapping data in this study and widely used by us15, 27 and others 28. Additionally, because of a single uniform cellular model used across the atria in the computer model, APDs in some regions (eg, distal side of PV sleeves) may not match well between modeling and optical mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such studies are the San Diego rabbit model [117] and the Auckland swine model [118]. Similarly, detailed models of human atria are also available [119]. More recently, individual geometries of the hearts are obtained by magnetic resonance imaging like e. g. in the Oxford rabbit model [29].…”
Section: Homogeneous Isotropic Tissuementioning
confidence: 99%
“…FEM and FVM are both very well suited for spatial discretizations of complex geometries with smooth representations of the boundaries, which is a key feature when polarization patterns induced via extracellularly applied currents are to be studied. Both FVM and FEM have been used to model electrical activity in anatomical realistic models of the atria (Harrild & Henriquez, 2000;Seemann et al, 2006;Vigmond et al, 2004;Virag et al, 2002) as well as the ventricles (Ashihara et al, 2008;Plank et al, 2009;Potse et al, 2006;Ten Tusscher et al, 2007). Mesh generation requirements are similar for both techniques, that is, the domain of interest has to be tessellated into a set of non-overlapping and conformal geometric primitives (Fig.…”
Section: Spatial Discretizationmentioning
confidence: 99%
“…5). With the FVM, quadrilaterals in 2D (Harrild & Henriquez, 1997) and hexahedral elements in 3D (Harrild & Henriquez, 2000;Trew, Le Grice, Smaill & Pullan, 2005) have been preferred, whereas with the FEM, triangles and quadrilaterals were used in 2D and tetrahedral or hexahedral elements in 3D (Munteanu et al, 2009;Seemann et al, 2006). Typically, monolithic meshes consisting of one element type only were used, but exception exist Rocha et al, 2011) where hybrid meshes consisting of tetrahedra, hexahedra, pyramids and prisms were used.…”
Section: Spatial Discretizationmentioning
confidence: 99%